4,4′-Bis[2-(3,4-dibutyl-2-thienylethynyl)]biphenyl - Liu, Lei (International Union of Crystallography, 2008)
The molecule of the title compound, C(40)H(46)S(2), reveals C (i) symmetry. An inversion centre is located at the mid-point of the C—C bond of the biphenyl unit; the asymmetric unit comprises one-half of the molecule. The conjugated backbone is nearly planar, with a mean deviation of 0.041 Å.